Bio-based Substances From Compost as Reactant and Active Phase for Selective Capture of Cationic Pollutants From Waste Water - Magnacca, Giuliana; Neves Dos Santos, Flavio; Sadraei, Razieh (Frontiers in Chemistry, 2020)
Alumina porous monoliths were successfully fabricated using a simple and reproducible synthesis dispersing gamma alumina phase from commercial boehmite (GAB) in water containing water-soluble bio-based substances (BBSs) obtained from composted biowaste. The wet mixture obtained was shaped in form of small spheres and then dried and calcined at 500°C in order to burn the organic matter and obtain mesoporous monoliths. They were successively functionalized with BBSs in order to introduce BBS functional groups and obtain an efficient adsorbing system. Therefore, in this work, BBSs acted as template/binder for the production of monoliths and as functionalizing agent of the produced monoliths. The reference powders, deeply studied in a published article (Sadraei et al., 2019b), and the monoliths of GAB before and after functionalization were characterized by means of x-ray diffraction to evidence their crystal structure, Fourier transform infrared spectroscopy for evaluating the presence of BBSs on the supports, thermogravimetric analysis to measure the thermal stability of the materials and quantify the functionalizing BBS amount immobilized on the supports, nitrogen adsorption at 77 K for the investigation of the surface area and porosity of the systems, and zeta potential measurements to analyze the effect of BBS immobilization on the surface charge of the supports and to predict the type of interaction, which can be established with substrates. Finally, the systems were applied in removal of pollutants with different charge, polarity, and molecular structure, such as dyes (crystal violet and acid orange 7) and contaminants of emerging concern (carbamazepine and atenolol). Only the cationic dye CV is captured by the adsorbing material, and this allows envisaging a possible use of the functionalized monoliths for selective adsorption of cationic substrates.